Effects of perioperative oxycodone as the sole opioid on immunity within a multi-modal analgesia framework in patients undergoing cervical cancer surgery: A randomised controlled trial - Jingjing Liu; Sumeng Chen; Jianxiao Chen; Hailian Liu; Weiyi Li; Haomin Chi; Xiaowei Ding; Shaoqiang Huang (Indian Journal of Anaesthesia)
Background and Aims: Current views on oxycodone’s effects on immunity are inconsistent. Our objective was to compare the effects of perioperative oxycodone as the sole opioid in a multi-modal analgesia regimen with conventional opioid regimens on immunity in cervical cancer. Methods: In this randomised controlled trial (RCT), patients scheduled for laparoscopic radical hysterectomy for cervical cancer were randomised to receive either oxycodone (Group O) or conventional opioid regimens (Group C). The primary outcome was the CD4+/CD8+ ratios postoperatively at 24 and 48 h. Student’s t-test was used for normally distributed variables, the non-parametric Wilcoxon test for non-normally distributed variables, and Chi-square/Fisher’s exact test for qualitative variables, with differences significant set at P < 0.05. Results: We included 56 patients in the final analysis. The postoperative CD4+/CD8+ ratios were comparable between groups. However, the mean arterial pressures (MAPs) at extubation and 5 minutes thereafter were lower in Group O than in Group C (both P < 0.001), as were the heart rates (HRs) (P = 0.001 and 0.018, respectively). Within 24 h postoperatively, the visual analogue scale (VAS) scores for resting and movement-evoked pain were lower in Group O than in Group C (all P < 0.001), and the same was observed at 48 h postoperatively (both P = 0.002), as was the incidence of catheter-related bladder discomfort (P = 0.001). The VASs for postoperative analgesia satisfaction were higher in Group O than in Group C (P = 0.006). Conclusion: In laparoscopic surgery for cervical cancer, perioperative oxycodone as the sole opioid within a multi-modal analgesia framework does not yield anticipated benefits in immunopreservation compared to conventional opioid regimens but improves postoperative pain management and haemodynamic stability.